TORREFACTION OF PALM KERNEL SHELL IN THE ABSENCE AND PRESENCE OF OXYGEN AND CARBON DIOXIDE - SAADON, SHAZLEEN (2016)
Despite the fact that torrefaction is a promising technique to improve the properties of biomass for energy conversion, the effect of atmospheric condition is not broadly explored.